Mechanical Properties of Sandwiched Construction with Composite and Hybrid Core Structure - Emad Kadum Njim; Hussam Raad Hasan; Muhsin J. Jweeg; Muhannad Al-Waily; Alaa Ali Hameed; Ahmed M. Youssef; Fahmi M. Elsayed (Advances in Polymer Technology)
In the field of lighter substitute materials, sandwich plate models of composite and hybrid foam cores are used in this study. Three core structures: composite core structure and then the core is replaced by a structure of a closed and open repeating cellular pattern manufactured with 3D printing technology. It finally integrated both into one hybrid open-cell core filled with foam and employed the same device (WBW-100E) to conduct the three-point bending experiment. The test was conducted based on the international standard (ASTM-C 393-00) to perform the three-point bending investigation on the sandwich structure. Flexural test finding, with the hybrid polyurethane/polytropic acid (PUR/PLA) core, the ultimate bending load is increased by 127.7% compared to the open-cell structure core. In addition, the maximum deflection increased by 163.3%. The simulation results of three-point bending indicate that employing a hybrid combination of PUR-PLA led to an increase of 382.3%, and for PUR–TPU by 111.8%; however, the highest value recorded with PUR/PLA, which has the slightest stress error among the tests. Also, it is reported that when the volume fraction of reinforced aluminum particles is increased, the overall deformation becomes more sufficient, and the test accuracy improves; for example, rising from 0.5% to 3%, the midspan deflection of composite (foam-Al) is increased by 40.34%. There were noticeable improvements in mechanical properties in the 2.5% composite foam-Al.